1982
DOI: 10.1111/j.1532-5415.1982.tb03381.x
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Hypersensitivity Skin Reactions in the Elderly

Abstract: A delayed hypersensitivity response to skin tests was observed in 47 healthy elderly participants in a geriatric screening clinic. Forty-four subjects (94 per cent) reacted to at least one antigen. It was concluded that anergy is uncommon in the healthy elderly and should not be considered a normal aging phenomenon.Data regarding the incidence of anergy or delayed hypersensitivity skin reactions in an ambulant elderly population appear to be conflicting. Four have shown that from 0 to 36 per cent of healthy el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

1983
1983
1991
1991

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…Although the elderly group responded to fewer antigens, it must be emphasized that 93% of our chronically ill aged subjects had one or more positive DCH responses, indicating that cellular‐mediated immunity is still functional. This high percentage of reactivity is similar to other studies where five or more antigens were used 4–6 …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although the elderly group responded to fewer antigens, it must be emphasized that 93% of our chronically ill aged subjects had one or more positive DCH responses, indicating that cellular‐mediated immunity is still functional. This high percentage of reactivity is similar to other studies where five or more antigens were used 4–6 …”
Section: Discussionsupporting
confidence: 89%
“…A battery of at least four to six antigens has been recommended to prevent a false diagnosis of anergy 7,8 . Lichtenstein et al 6 reported that 94% of an elderly population reacted to at least one DCH antigen when a total of five antigens were applied. When Cohn et al 4 used eight antigens in 29 elderly nursing home residents, all but one had at least one positive response.…”
Section: Discussionmentioning
confidence: 99%
“…The immunocompetence of aging experimental animals and humans has been studied by many investigators 3–25 . Although there are significant changes in other components of the immune system (see below), the major defects appear to arise in the T‐lymphocyte population 10,14,16–20 .…”
Section: Discussionmentioning
confidence: 99%
“…Cells from aged experimental animals or humans are less capable of eliciting graft‐versus‐host reactions 27 in response to allogeneic lymphocytes 27 and soluble antigens 26 . In addition, some reports suggest that delayed hypersensitivity in response to Candida albicans , PPD (purified protein derivative), and mumps 21 is also impaired. This latter point, however, is contested by other investigators.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous authors have observed decreased cutaneous delayed hypersensitivity in the elderly 1–7 . These studies have had uncertain applicability to the nursing home population, since they have examined either healthy older persons in the community or hospitalized patients, or have used only a limited number of antigens.…”
mentioning
confidence: 99%